Pengaruh Blended Learning Terhadap Kualitas Pembelajaran Pada Mata Pelajaran PAI di SMAN 5 Tambun Selatan - Annisa Roesmin; Muhammad Arifin Rahmanto; Shobah Shofariyani Iryanti (Jurnal Pendidikan Islam, 2022)
This study aims to determine the effect of blended learning on the quality of PAI learning at SMAN 5 Tambun Selatan. This research is a quantitative research through Validity Test, Reliability, Normality, Linearity, Hypothesis Test, Coefficient of Determination and Simple Linear Regression using SPSS version 25 application software. Samples were taken by Non Probability Sampling Technique namely Purposive Sampling as many as 122 students. The Blended Learning research instrument for the quality of PAI learning uses a questionnaire distributed through the Google Form application. The results of simple linear regression calculations are 0.000 <0.05 with a significance value of <0.05, so it can be concluded that the two variables influence each other. With a correlation of determination, namely 0.473, the interpretation obtained is that the correlation is sufficient. Testing the H1 hypothesis is accepted, meaning that Blended Learning has an influence on the quality of PAI learning.